Syndrome Sinistre: Left Brachiocephalic Vein Compression and its Neurological Manifestations - Karthikeyan M. Arcot; Vincent S. DeOrchis (MDPI AG, 2024)
Embryologically, the left brachiocephalic vein (LBV) originates as an anastomotic channel between the right and left anterior cardinal veins. This positions the LBV between the manubrium sterni anteriorly and the innominate artery posteriorly. This pattern of adjacency of the aorta to the LBV is unique to mammals and results from a quirk of evolution. With age, the ascending aorta unfolds, elongates and dilates. Simultaneously, there is a change in the thoracic geometry that reduces the thoracic volume primarily from disc height loss and kyphosis. These transitions progressively compress the LBV. Normally, this compression is circumvented via collateral pathways and "Blood finds a way". However, traversing these circuitous pathways comes at a cost and can result in delayed transit times and venous congestion. While it is possible that compression of the LBV in the setting of adequate collateral channels may fail to provoke any pathologic sequelae, we propose a phenomenon in which such compression in the setting of inadequate collateral circulation may lead to a state of pathologic venous congestion. This anatomic anomaly and its associated clinical features, if identified, can offer a new avenue for treatment options for some of the hitherto unexplained neurologic disorders.